Information Systems for eGovernment A Quality-of-Service Perspective - Viscusi, Gianluigi; Batini, Carlo; Mecella, Massimo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
The success of public sector investment in eGovernment initiatives strongly depends on effectively exploiting all aspects of ICT systems and infrastructures. The related objectives are hardly reachable without methodological frameworks that provide a holistic perspective and knowledge on the contexts of eGovernment initiatives. Yet public administrators usually have a mix of legal and administrative knowledge, while lacking an information systems background. With this book, Viscusi, Batini and Mecella provide a comprehensive methodology for service-oriented information systems planning, with special emphasis on eGovernment initiatives. They present the eG4M methodology which structurally supports the development of optimal eGovernment plans, considering technological, organizational, legal, economic and social aspects alike. The approach is focused on two pillars: the quality of the provided services and related processes, and the quality of the data managed in the administrative processes and services. The book is written for public administrators, decision-makers, practitioners, ICT professionals and graduate students, providing a comprehensive perspective of the challenges, opportunities and decisions related to strategic and operational planning of service-oriented information systems in eGovernment.
eGovernment: A Complex Challenge -- The Different Facets of eGovernment Initiatives: Paradigms and Approaches -- Data Governance -- The eG4M Methodology at a Glance -- Strategic Planning -- eGovernment Vision Elicitation -- State Reconstruction -- eReadiness Assessment -- Quality Assessment -- Operational Planning -- Definition of Priority Services and Value Targets -- Choice of Projects -- A Reference Technological Architecture -- Guidelines for the Specification of New Administrative Processes -- eGovernment in Mediterranean Countries Public Administrations: Case Studies -- eGovernment Initiatives in Italy -- Tunisian Ministry of Agriculture Planning of New Services and Information Systems Integration.
Keywords: Computer science; Information systems; Information Systems; Management information systems; Computer Science; Information Systems Applications (incl. Internet).; Business Information Systems; Management of Computing and Information Systems; Computer Appl. in Administrative Data Processing